Evaluation of symptom control in chronic obstructive pulmonary disease after reinforcement of proper inhaler technique - Tanya Jaiswal; Sparsh Gupta; Pooja Anand; Pranav Ish; Dhruv Sakkarwal; Divya Sahu (Monaldi Archives for Chest Disease)
Chronic obstructive pulmonary disease (COPD) remains a leading cause of morbidity and mortality worldwide. Proper inhaler technique is a critical component of effective COPD management, yet it is often suboptimal in clinical practice. This study aimed to evaluate the impact of reinforcing proper inhaler techniques on COPD symptom control. This was a pre-post, prospective study conducted in the Department of Pharmacology at a tertiary care hospital in Delhi. A total of 118 COPD patients using inhalers were enrolled. A prospective study of 118 COPD patients using either dry powder inhalers or metered dose inhalers was carried out in the outpatient clinic of our hospital. Participants received structured demonstrations of proper inhaler technique at baseline (day 0), week 4, and week 8, with final evaluations at week 12. Symptom control was assessed using the COPD Assessment Test (CAT) score, and inhaler technique was evaluated using the Inhaler Technique Score (ITS). Adverse effects were monitored and documented. The study demonstrated a significant improvement in both CAT and ITS scores over the 12-week follow-up. The proportion of participants achieving optimal CAT scores (0-10) increased from 4.24% at baseline to 12.7% by week 12. Concurrently, the percentage of participants scoring the maximum ITS of 10 increased from 0% at baseline to 90.7% by week 12. Adverse effects were minimal, with 92.37% of participants reporting no adverse effects. A negative correlation was observed between changes in ITS and CAT scores, highlighting the effectiveness of the intervention in improving COPD symptom control. In conclusion, reinforcing proper inhaler technique through structured educational interventions significantly improves COPD symptom control, as evidenced by enhanced CAT and ITS scores. This study emphasizes the need for routine education and reinforcement of inhaler use in COPD management to achieve optimal clinical outcomes.